Relativistic Thermodynamic Properties of Interacting Fermi Gas in a Strong Magnetic Field (Journal of Atomic and Molecular Sciences, 2014)
Based on the Mean Field Theory, the relativistic thermodynamic potentialfunction (RTPF) of interacting Fermi gases in a strong magnetic field is derived. Onthis basis, by taking the interacting term from the RTPF and using the thermodynamicrelations, analytical expressions of the energy, the heat capacity and the chemical potentialare calculated at low temperatures. And combined with numerical simulationanalysis, the effect of interaction on the thermodynamic properties of the system is analyzedand the regulation mechanisms on the interaction impacts of both the magneticfield and the relativistic effect are discussed.
Keywords: interaction strong magnetic field; relativity effect; Fermi gas.